Activated Internal Alkyne‐Based Polymerization†. Issue 16 (20th June 2022) - Li, Baixue; Wang, Jia; He, Benzhao; Qin, Anjun; Tang, Ben Zhong
Comprehensive Summary: As an emerging and efficient polymerization methodology, activated internal alkyne‐based polymerization has been considered as a powerful tool for the construction of polymers with diverse architectures and versatile functions. This review focuses on the recent progresses in the polymerization using mono‐activated, di‐activated, in‐situ generated, ring‐strained ethynyl groups as substrates, coupling with post‐modification on premade polymers containing activated internal ethynyl moieties. Representative examples are used to illustrate the fundamental design strategy, the development of polymerization and post‐functionalization, along with the properties and potential applications of the prepared polymers. Moreover, the challenges and perspectives in terms of new‐type active alkynes, green polymerization methodology, tailored regio‐/stereoselectivity modulation, and potentially expanded application in this area are also discussed. Abstract : The recent progresses in the polymerization using activated internal alkynes, together with post‐modification on preformed polymers containing activated internal acetylene moieties were summarized. Through discussion of representative examples, it is hoped to provide a powerful tool for the preparation of new polymers with well‐defined structures, advanced functions, and versatile applications.